Power game - Feehan, Christine (Feehan, Christine. GhostWalker novel., 2017)
"#1 New York Times bestselling author Christine Feehan is "one of the best storytellers around" (RT Book Reviews). Find out why as two lovers surrounded by greed and corruption discover there's no telling whom you can trust--or who will come out on top... When members of a United Nations joint security force are taken hostage by radical terrorists in Indonesia, Captain Ezekiel Fortunes is called to lead the rescue team. Part of a classified government experiment, Zeke is a supersoldier with enhanced abilities. He can see better and run faster than the enemy, disappear when necessary and hunt along any terrain. There are those in the world willing to do anything for power like that... A formidable spy genetically engineered to hide in plain sight, Bellisia rarely meets a man who doesn't want to control her or kill her. But Zeke is different. His gaze, his touch--they awaken feelings inside her that she never thought possible. He's the kind of man she could settle down with--if she can keep him alive.."--